2015
DOI: 10.1007/s11255-015-1014-0
|View full text |Cite
|
Sign up to set email alerts
|

Right versus left retroperitoneoscopic living-donor nephrectomy

Abstract: Although larger sample sizes would be required to evaluate postoperative complication rate, these results indicate that both the right and left RDN could be performed with similar donor and recipient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…No case of graft vascular thrombosis was observed. These results are consistent with those of most studies [14][15][16][17][18][19][20], except for studies [21,22] based on national registries in which Khalil [21] reported a higher rate of vascular thrombosis and DGF for right kidneys. However, this difference was minor (graft thrombosis: 0.8 vs. 1.1% and DGF: 4.2 vs. 5.7%) and did not affect the 1-year graft survival.…”
Section: Discussion/conclusionsupporting
confidence: 90%
See 1 more Smart Citation
“…No case of graft vascular thrombosis was observed. These results are consistent with those of most studies [14][15][16][17][18][19][20], except for studies [21,22] based on national registries in which Khalil [21] reported a higher rate of vascular thrombosis and DGF for right kidneys. However, this difference was minor (graft thrombosis: 0.8 vs. 1.1% and DGF: 4.2 vs. 5.7%) and did not affect the 1-year graft survival.…”
Section: Discussion/conclusionsupporting
confidence: 90%
“…No difference in OT was observed in our series. Some series [14,18] have reported cases of conversion due to bleeding following a vascular injury, but with no significant difference compared to left nephrectomy. No case of conversion or intraoperative transfusion was observed in our series.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The trends now show that laparoscopic technique is now almost universally practiced. Hybrid variations of laparoscopic techniques have emerged over time including retroperitoneoscopic living donor nephrectomy, with a recent report showing no significant differences in outcomes between right‐ vs. left‐sided procedures . Our UNOS database analysis interestingly shows that in terms of donor vascular complications, there was no significant difference between left‐and right‐sided nephrectomies.…”
Section: Discussionmentioning
confidence: 71%
“…Nevertheless, the debate on the safety, efficacy, and potential advantages of choosing the right or left kidney for LDN is still open [[18], [19], [20]]. In this sense, the first and largest study to compare living donor and recipient outcomes specifically based on laterality in today’s laparoscopic era, showed certain statistical differences in terms of recipient´s rejection rate, delayed graft function, and one-year graft survival in favor of the left side nephrectomy, although the magnitude of difference was extremely small.…”
Section: Discussionmentioning
confidence: 99%